2018
DOI: 10.32404/rean.v5i3.2077
|View full text |Cite
|
Sign up to set email alerts
|

INTERFERÊNCIA DE CULTURAS ANUAIS NO CRESCIMENTO INICIAL DE Brachiaria ruziziensis

Abstract: Objetivou-se avaliar o crescimento inicial da B. ruziziensis consorciada com espécies anuais. O experimento foi conduzido na Embrapa Agropecuária Oeste, em Dourados-MS. Em 18/05/2014 semeou-se a B. ruziziensis solteira e consorciada com aveia branca, trigo, canola, girassol, crambe e Crotalaria ochroleuca, com seis plantas por vaso; e milheto, feijão-caupi, feijão-comum, sorgo sacarino e milho com quatro plantas por vaso, contendo 30 kg de solo seco. O arranjo experimental foi em esquema fatorial 2x12 (Solos (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
1
0
2
Order By: Relevance
“…Beyond the lack of available rainfall, the shading by the established rice crop may have reduced the photosynthetic rate of forage grass and, consequently, its dry matter yield. This intercrop response pattern was previously reported for U. ruziziensis and many other cash crops, such as sunflower (Souza et al, 2015), soybean (Erasmo et al, 2017), and maize (Ribeiro et al, 2018). These authors reported reduced forage yield due to shading.…”
Section: Forage Production Of U Ruziziensissupporting
confidence: 83%
“…Beyond the lack of available rainfall, the shading by the established rice crop may have reduced the photosynthetic rate of forage grass and, consequently, its dry matter yield. This intercrop response pattern was previously reported for U. ruziziensis and many other cash crops, such as sunflower (Souza et al, 2015), soybean (Erasmo et al, 2017), and maize (Ribeiro et al, 2018). These authors reported reduced forage yield due to shading.…”
Section: Forage Production Of U Ruziziensissupporting
confidence: 83%
“…In the experimental conditions, there was no significant difference in the corn biomass (Table 3), indicating that the competition for water and nutrients among the brachiaria plants in the row did not influence the performance and yield of the corn plants. The biomass production of U. ruziziensis was higher in the single cultivation than brachiaria in intercropping systems (Ribeiro et al, 2018). In the intercropping conditions, in interspersed rows and/or in the same row, the brachiaria biomass production was higher than the U. ruziziensis sowing between the corn rows (Table 3).…”
Section: Resultsmentioning
confidence: 92%
“…O consórcio é uma técnica na qual mostra-se viável ao controle de plantas daninha, auxilia ainda, na conservação do solo e na adubação orgânica propiciando a recuperação deste (BARBOSA JUNIOR et al, 2019). Um exemplo de sistema consorciado é o cultivo de culturas como girassol e feijão comum, essas culturas , tiveram um melhor desenvolvimento quanto cultivadas isoladamente (RIBEIRO et al, 2018). Os agricultores de Canudos citaram que o cultivo em consórcio poupa espaço e diminui as prováveis perdas totais, algo de extrema importância para uma população carente de recursos financeiros.…”
Section: Resultsunclassified